Penerapan Algoritma Kalman Filter dalam Prediksi Kecepatan Angin di Kota Balikpapan - Fitria, Irma; Hasanah, Primadina (SPECTA Journal of Technology, 2017)
One of the climate?s elements that has an influence on daily activities is the wind speed. Wind is a movement of air that flows from high pressure to low pressure region. In the shipping and aviation, wind speed is a very important thing to predict. This is due to the wind speed is very influential on the process of the transportation activities. A strong wind can disturb the fluency of transportation. Therefore, information regarding the wind speed prediction is very important to know. In this paper, Kalman Filter algorithm is applied in the wind speed prediction by taking the case in Balikpapan. In this case, the Kalman Filter algorithm is applied to improve the result of ARIMA prediction based on error correction, so we get the prediction result, called ARIMA-Kalman Filter. Based on the simulation result in this study, it can be shown that the prediction result of ARIMA-Kalman Filter is better than ARIMA?s. This is known from the level of accuracy from ARIMA-Kalman Filter, which increased about 65% from ARIMA result.